QTL analysis for carcass composition and meat quality traits on SSC7q1.1-q1.4 region in Large White × Meishan F2 pigs - W. Huang; Z. Xu; Y. Xiong; B. Zuo (Czech Journal of Animal Science, 2012)
Significant QTL for carcass and meat quality traits on Sus scrofa chromosome 7 (SSC7) were detected in various Meishan derived resource populations, especially on q1.1-q1.4 region. In order to confirm and narrow the QTL in this region, seven single-nucleotide polymorphisms (SNPs) and one insertion or deletion located in eight genes (BTNL1, SLC39A7, COL21A1, PPARD, GLP1R, MDFI, GNMT, and PLA2G7) were included for linkage mapping in a Large White × Meishan resource population, as well as two flanking microsatellite markers (SW2155 and SW352). Ten chromosome-wise significant QTL and two suggestive QTL were found. QTL affecting carcass weight and dressing percentage were mapped within the interval BTNL1 and SLC39A7. QTL for skin weight and percentage, bone weight and percentage in carcass were located between the interval PPARD and GLP1R. QTL for fat weight and percentage in carcass were detected between GNMT and PLA2G7 genes, while QTL for loin muscle width was found between GLP1R and MDFI. The results of this study will help to facilitate identifying the causative molecular genetic variation in this region.